Determining the frequency of free vibrations of turbine blades by finite element method - Бородачов, М.М.; Доник, Т.В. (Proceedings of National Aviation University (archive), 2007)
The problem about a presence of frequencies of free fluctuations the blades turbines is considered. Influence of presence of a crack on frequencies of free fluctuations is investigated.